New chromosome counts and genome size estimates for 28 species of Taraxacum sect. Taraxacum - Macháčková, Petra; Majeský, Ľuboš; Hroneš, Michal; Hřibová, Eva; Bohumil Trávníček; Vašut, Radim J (Comparative cytogenetics, 2018)
The species-rich and widespread genus Taraxacum F. H. Wiggers, 1780 (Asteraceae subfamily Cichorioideae) is one of the most taxonomically complex plant genera in the world, mainly due to its combination of different sexual and asexual reproduction strategies. Polyploidy is usually confined to apomictic microspecies, varying from 3x to 6x (rarely 10x). In this study, we focused on Taraxacum sect. Taraxacum (= T.sect.Ruderalia; T.officinale group), i.e., the largest group within the genus. We counted chromosome numbers and measured the DNA content for species sampled in Central Europe, mainly in Czechia. The chromosome number of the 28 species (T.aberrans Hagendijk, Soest & Zevenbergen, 1974, T.atroviride Štěpánek & Trávníček, 2008, T.atrox Kirschner & Štěpánek, 1997, T.baeckiiforme Sahlin, 1971, T.chrysophaenum Railonsala, 1957, T.coartatum G.E. Haglund, 1942, T.corynodes G.E. Haglund, 1943, T.crassum H. Øllgaard & Trávníček, 2003, T.deltoidifrons H. Øllgaard, 2003, T.diastematicum Marklund, 1940, T.gesticulans H. Øllgaard, 1978, T.glossodon Sonck & H. Øllgaard, 1999, T.guttigestans H. Øllgaard in Kirschner & Štěpánek, 1992, T.huelphersianum G.E. Haglund, 1935, T.ingens Palmgren, 1910, T.jugiferum H. Øllgaard, 2003, T.laticordatum Marklund, 1938, T.lojoense H. Lindberg, 1944 (= T.debrayi Hagendijk, Soest & Zevenbergen, 1972, T.lippertianum Sahlin, 1979), T.lucidifrons Trávníček, ineditus, T.obtusifrons Marklund, 1938, T.ochrochlorum G.E. Haglund, 1942, T.ohlsenii G.E. Haglund, 1936, T.perdubium Trávníček, ineditus, T.praestabile Railonsala, 1962, T.sepulcrilobum Trávníček, ineditus, T.sertatum Kirschner, H. Øllgaard & Štěpánek, 1997, T.subhuelphersianum M.P. Christiansen, 1971, T.valens Marklund, 1938) is 2n = 3x = 24. The DNA content ranged from 2C = 2.60 pg (T.atrox) to 2C = 2.86 pg (T.perdubium), with an average value of 2C = 2.72 pg. Chromosome numbers are reported for the first time for 26 species (all but T.diastematicum and T.obtusifrons), and genome size estimates for 26 species are now published for the first time.
Keywords: flow cytometry; chromosome number; karyology; Asteraceae; Taraxacum officinale